Endothelial cell provenance: an unclear role in transplant medicine - Pace, Autumn; Steiner, Marie E.; Vercellotti, Gregory M.; Somani, Arif (Frontiers in Transplantation, 2023)
An understanding of the interplay between both donor endothelial progenitors and the recipient endothelium (in the case of hematopoietic cell transplant) and recipient endothelial provenance upon the established donor endothelium (in the case of solid organ transplant) is unknown. It is postulated that this interplay and consequences of purported dual endothelial populations may be a component of the post-transplant disease process and contribute to complications of engraftment or rejection. To address this potential confounding and often overlooked arena of vascular biology, a directed brief overview primarily focused on literature presented over the last decade is presented herein.